Inactivation of the PD-1-Dependent Immunoregulation in Mice Exacerbates Contact Hypersensitivity Resembling Immune-Related Adverse Events - Ashoori, Matin Dokht; Suzuki, Kensuke; Tokumaru, Yosuke; Ikuta, Naoko; Tajima, Masaki; Honjo, Tasuku; Ohta, Akio (Frontiers in Immunology, 2021)
Blockade of PD-1, an indispensable physiological immunoregulatory mechanism, enhances immune activities and is widely used in the immunotherapy of cancer. This treatment often accompanies inflammatory complication called immune-related adverse events (irAE), most frequently in the skin. To analyze how skin inflammation develops by the blockade of PD-1-dependent immunoregulation, we studied the exacerbation of oxazolone-induced contact hypersensitivity by PD-L1 blockade. The inactivation of PD-1 signaling enhanced swelling of the skin with massive CD8+ T cell infiltration. Among PD-1-expressing cells, T cells were the predominant targets of anti-PD-L1 mAb treatment since PD-L1 blockade did not affect skin inflammation in RAG2-/- mice. PD-L1 blockade during immunization with oxazolone significantly promoted the development of hapten-reactive T cells in the draining lymph nodes. The enhancement of local CD8+ T cell-dominant immune responses by PD-L1 blockade was correlated with the upregulation of CXCL9 and CXCL10. Challenges with a low dose of oxazolone did not demonstrate any significant dermatitis; however, the influence of PD-L1 blockade on T cell immunity was strong enough to cause the emergence of notable dermatitis in this suboptimal dosing, suggesting its relevance to dermal irAE development. In the low-dose setting, the blockade of CXCR3, receptor of CXCL9/10, prevented the induction of T cell-dominant inflammation by anti-PD-L1 mAb. This experimental approach reproduced CD8+ T cell-dominant form of cutaneous inflammation by the blockade of PD-L1 that has been observed in dermal irAE in human patients.